2021
DOI: 10.1371/journal.pone.0260765
|View full text |Cite
|
Sign up to set email alerts
|

Polydextrose with and without Bifidobacterium animalis ssp. lactis 420 drives the prevalence of Akkermansia and improves liver health in a multi-compartmental obesogenic mice study

Abstract: The past two decades of research have raised gut microbiota composition as a contributing factor to the development of obesity, and higher abundance of certain bacterial species has been linked to the lean phenotype, such as Akkermansia muciniphila. The ability of pre- and probiotics to affect metabolic health could be via microbial community alterations and subsequently changes in metabolite profiles, modulating for example host energy balance via complex signaling pathways. The aim of this mice study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In an NMR study of the effects of prebiotics and probiotics on liver health in obesogenic mice, Bifidobacterium animalis ssp. lactis 420 administration was found to significantly regulate the hepatic levels of betaine, taurine, and choline ( Yde et al, 2021 ). In our work, Christensenella regulates mRNA expressions of G6PC and PEPCK in liver, levels of hepatic glycogen, and blood glucose and lipid.…”
Section: Discussionmentioning
confidence: 99%
“…In an NMR study of the effects of prebiotics and probiotics on liver health in obesogenic mice, Bifidobacterium animalis ssp. lactis 420 administration was found to significantly regulate the hepatic levels of betaine, taurine, and choline ( Yde et al, 2021 ). In our work, Christensenella regulates mRNA expressions of G6PC and PEPCK in liver, levels of hepatic glycogen, and blood glucose and lipid.…”
Section: Discussionmentioning
confidence: 99%
“…Later NMR foodomics studies have subsequently substantiated the potential of inulin to stimulate SCFAs production in the gut where inclusion of inulin in both general diets and in a yogurt matrix has been shown to increase SCFAs production [24 ▪ ,25 ▪ ]. In addition, NMR foodomics has also contributed to document how inclusion of other dietary ingredients or components such as dietary fiber [26], polysaccharides [27,28], polydextrose [29 ▪ ], anthocyanins [30 ▪ ] and chick pea extract [31 ▪ ] stimulate metabolic activity in the gut (Table 1).…”
Section: Modulation Of Foodsmentioning
confidence: 99%
“…After 12 weeks, it was found that the sexual hormone binding protein in the test group was increased, the hirsutism score was reduced by R, insulin sensitivity was increased, and the lipoprotein was reduced, indicating that the intervention treatment of probiotics had a certain effect on PCOS patients. In the dietinduced model of diabetes and obese mice, B. lactis B420 strain has been proved to help improve insulin resistance and reduce fat content (Yde et al, 2021). It has been found in clinical studies that the use of B. lactis can improve the sex hormone level of PCOS patients.…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%